Kidney sparing surgery versus radical nephroureterectomy in upper tract urothelial carcinoma: a meta-analysis and systematic review - Zhou, Leqing; Huang, Chuyang; Sun, Sheng; Ning, Keping; Tang, Shan (Frontiers in Oncology, 2025)
ObjectiveKidney-sparing surgery (KSS) has been increasingly performed in patients with upper tract urothelial carcinoma (UTUC) in recent years. We aim to conduct a systematic review and meta-analysis comparing the long-term oncologic and renal function outcomes of KSS with those of radical nephroureterectomy (RNU) for UTUC.Materials and methodsA literature search was conducted on PubMed, Embase, and Web of Science in January 2024. A meta-analysis was performed to analyze overall survival (OS), cancer-specific survival (CSS), recurrence-free survival (RFS), intravesical recurrence-free survival (IVRFS), metastasis-free survival (MFS), and surgery-related estimated glomerular filtration rate (eGFR) variations.ResultsA total of 32 studies with 21615 patients were included in this meta-analysis. Patients treated with KSS were less likely to have hydronephrosis, more often had low-grade tumors, and were more frequently at a low-stage compared to those undergoing RNU. There were no significant differences between the KSS and RNU groups in terms of 5-year OS, 5-year CSS, 5-year RFS, 5-year IVRFS, 5-year MFS, and hazard ratios (HRs) for OS and CSS based on univariate or multivariable Cox regression analysis. Similar results were found in subgroup analyses comparing segmental urethrectomy (SU) with RNU. In the comparison between the endoscopic management (EM) and RNU groups, EM was associated with worse overall survival outcomes (HR,1.40; 95%CI,1.08-1.82; P=0.01) based on multivariable Cox regression analysis, and the upper tract recurrence rate (OR,39.06; 95%CI, 14.55-104.85; P<0.00001) was significantly higher in the EM group. On the other hand, in patients treated with KSS, postoperative renal function as measured by eGFR increased by 0.4ml/min/1.73 m2, while it decreased by 11.4ml/min/1.73 m2 in the RNU group (WMD, 11.81 ml/min/1.73 m2; 95%CI,9.06-14.56; P<0.0001).ConclusionOur meta-analysis supports similar oncological outcomes between KSS and RNU, although tumor characteristics were not equally balanced. KSS can be considered the best choice option for patients with low-risk UTUC, as it offers better preservation of renal function. In terms of kidney-sparing options, SU could be a better alternative for the treatment of ureteral tumors compared to ureteroscopy, due to the higher local recurrence rate associated with EM.Systematic review registrationhttps://inplasy.com/inplasy-2024-5-0051/, identifier (INPLASY202450051).